Highly dense lead titanate ceramics from refined processing - Udomporn A. (2014)
Lead titanate (PbTiO3, PT) ceramic is a useful pyroelectric and piezoelectric material for high-temperature applications. However, it is very difficult to prepare a pure-phase and dense PT as a result of a high c/a ratio. In this study, conformable PT ceramics with 97% of the theoretical density were successfully synthesized by means of carefully controlled processing parameters that include sintering temperature, soaking time and heating/cooling rates. It can be found that these ceramics exhibit highly densified and uniform microstructure with the optimum conditions of 1225 °C sintering temperature, 2 h soaking time and 1 °C min-1 heating/cooling rates. Moreover, relatively inexpensive laboratory grade lead oxide (PbO) and titanium oxide (TiO2) can be used as starting materials. © 2003 Elsevier Ltd. All rights reserved.